Literally the hardest part about having a positive child is disclosure”: Child and family stigma management strategies among U.S. parents of internationally adopted children with perinatally-acquired HIV - Amanda R. Bingaman; Alison B. Hamilton; Rosemary Olivero; Claudia S. Crowell; Cynthia D. Fair (SSM: Qualitative Research in Health, 2022)
The number of internationally adopted children living with perinatally-acquired HIV (IACP) in the U.S. is increasing, yet little is known about their families' experiences. The goal of this paper is to examine the lived experiences of adoptive parents as they navigate disclosure. A purposive sample of parents of IACP was recruited at two pediatric infectious disease clinics and via closed Facebook groups. Parents completed two semi-structured interviews. Interview questions centered on HIV disclosure decisions and child adjustment. Interviews were analyzed using an iterative process. All parents (n ​= ​24) identified as white and 20 had transracial families, with children adopted from 11 different countries. Analyses revealed that anticipated and experienced stigma shaped disclosure decisions and influenced strategies to mitigate HIV stigma. Disclosure to the child and family members was a significant challenge. We identified six child-focused strategies to reduce stigma including incremental disclosure. Once a child knew their HIV status, parents shifted to contextualize societal views of HIV and prepared their child for negative comments. We identified two family-focused strategies: normalizing conversations about HIV as well as race and adoption and limiting disclosure beyond the home. Parents emphasized privacy while trying to avoid the shame that accompanies secrecy. Parents with IACP navigate complex terrain that includes not only their child's stigmatized health condition but also their adoptive status. Despite the identified strategies, families still encountered challenges in communities and healthcare settings. Families with IACP would benefit from health and social systems that support stigma management strategies to minimize potential for negative experiences.